Investigating the searching behavior of Sino-U.S. relations in China based on complex network - Chen, Jun; Wang, Lei; Weng, Wuyan (Frontiers in Physics, 2023)
The Sino-U.S. relationship is one of the most important bilateral relationships in the literature of global geopolitics. Not only the two countries, but also other nations in the relevant regions have been influenced by their economic, cultural, political, educational, and diplomatic relations. In this paper, we have applied Visibility Graph as the method, analyzed the data from Baidu searching index of the keyword “Sino-U.S. relations” from 2011 to 2021 into a directionless and authoritarian network, and studied its dynamic characteristics. from the time series data, it has been found that the relationship between the data is closer with more edges, greater degrees, and greater clustering coefficients. Meanwhile, the shorter the average path length, the closer the relationship between the data. The results provide a new perspective for analyzing the time series characteristics of Sino-U.S. relations.